Ruptured Subcapsular Liver Hematoma: A Rare Complication of HELLP Syndrome - Pratishtha Singh; Kayle Warren; Victor Collier (Case Reports in Hepatology)
Subcapsular liver hematoma (SLH) is a rare complication of HELLP (hemolysis, elevated liver enzymes, low platelets) syndrome. We report a previously healthy 16-year-old female presenting with pre-eclampsia requiring emergent C-section, who developed immediate postoperative bleeding and abdominal distention. Abdominal computed tomography angiography (CTA) revealed a large encapsulated liver hematoma with active extravasation. The patient was successfully treated with a multidisciplinary approach with medical and surgical management.